Contrasting multistage and computer-based testing: score accuracy and aberrant responding - Sideridis, Georgios; Ghamdi, Hanan; Zamil, Omar (Frontiers in Psychology, 2023)
The goal of the present study was to compare and contrast the efficacy of a Multistage (MST) design using three paths compared to a traditional computer-based testing (CBT) approach involving items across all ability levels. Participants were n=627 individuals who were subjected to both a computer-based testing (CBT) instrument and a measure constructed using multistage testing to route individuals of low, middle, and high ability to content that was respective to their ability level. Comparisons between the medium of testing involved person ability accuracy estimates and evaluation of aberrant responding. Results indicated that MST assessments deviated markedly from CBT assessments, especially for low and high-ability individuals. Test score accuracy was higher overall in MST compared to CBT although error of measurement was enhanced for high-ability individuals during MST compared to CBT. Evaluating patterns of responding indicated significant amounts of Guttman-related errors during CBT compared to MST using person-fit aberrant response indicators. It is concluded that MST is associated with significant benefits compared to CBT.